PENGARUH PERBANDINGAN BAHAN DENGAN PELARUT ASETON TERHADAP TOTAL FENOLIK, WARNA DAN KLOROFIL EKSTRAK Sargassum polycystum - Hernes, I Putu Fajardhiputra; Suhendra, Lutfi; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
Seaweed is one of the biological resources that its existence is very abundant in all marine waters in Indonesia. One of them is Sargassum polycystum which is a type of brown algae ( Phaeophyceae ). The purpose of this study was to determine the effect of comparison the material with the solvent to the color content, the total phenolic and chlorophyll of Sargassum polycystum extract, and to determine the comparative treatment of the material with best solvent to produce Sargassum polycystum extract. This experiment uses a simple Group Randomized Design (GRD) consisting 5 comparisons of materials with the acetone (w/v) ie (1:9), (1:11), (1:13), (1:15), (1:17). Furthermore, the treatment is repeated as much as 3 times based on implementation time, to obtained 15 units of experiments. The results showed the ratio of material with the solvent had a very significant effect (P<0.01) on the rendement parameters, brightness (L*), redness (a*), yellowishness (b *), total phenolic, chlorophyll a and total chlorophyll. The results had significant effect (P<0.05) shown on chlorophyll b parameters. The best treatment was obtained from the treatment with the highest value on several parameters tested ie, yield, total phenolic and chlorophyll content. Comparison of material with acetone solvent (1:15) (w/v) was the best treatment with yield of 2.27%, color intensity (L*) 5.08, (a*) -5.62, (b*) 54.00, total phenolic 0.95 mgGAE / 100g, chlorophyll a 279 ppm, chlorophyll b 134 ppm and total chlorophyll 310 ppm. Key words: Sargassum polycystum, compounds bioactive, comparison of material with solvent .